Low-carbon development : Latin American responses to climate change - Torre, Augusto de la; Fajnzylber, Pablo; Nash, John, 1953- (World Bank Latin American and Caribbean studies., 2009)
Governments and civil society in Latin America and the Caribbean should be well informed about the potential costs and benefits of combating climate change, their policy options over the next decades, and the global context for these policy decisions. At the same time, the global community needs to be better informed about the unique perspective of the Latin American and Caribbean region: problems the region will face, its potential contributions toward combating global warming, and how to maximize this potential while continuing to maintain growth and reduce poverty. This book, a companion vo.